2018
DOI: 10.1182/blood-2018-03-785972
|View full text |Cite
|
Sign up to set email alerts
|

How I treat breast implant–associated anaplastic large cell lymphoma

Abstract: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a recently described form of T-cell non-Hodgkin lymphoma now formally recognized by the World Health Organization classification of lymphoid neoplasms. The disease most often presents with a delayed seroma around the breast implant, almost exclusively with a textured surface, and manifests with breast pain, swelling or asymmetry, capsular contracture, but can also present with a breast mass, and lymph node involvement. The prognosis of BIA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 48 publications
(83 reference statements)
1
75
0
1
Order By: Relevance
“…A recent population‐based case‐control study based on the pathology registry in the Netherlands established that BI is associated with a markedly increased risk (400 times) of developing ALCL, but the absolute cumulative risk is estimated to one case for every 50 000 women with BI by the age of 50 years and one per 7000 by the age of 75 . In another study based on US cases, the lifetime risk of BIA‐ALCL in women with textured implants was estimated to be 1 in 30 000 …”
Section: Breast Implant‐associated Anaplastic Large Cell Lymphomamentioning
confidence: 99%
See 3 more Smart Citations
“…A recent population‐based case‐control study based on the pathology registry in the Netherlands established that BI is associated with a markedly increased risk (400 times) of developing ALCL, but the absolute cumulative risk is estimated to one case for every 50 000 women with BI by the age of 50 years and one per 7000 by the age of 75 . In another study based on US cases, the lifetime risk of BIA‐ALCL in women with textured implants was estimated to be 1 in 30 000 …”
Section: Breast Implant‐associated Anaplastic Large Cell Lymphomamentioning
confidence: 99%
“…However, lymphoma involvement is not proven by biopsy in all instances so that the actual incidence of locoreginal nodal dissemination is likely lower. Uncommonly, cutanous lesions or B sympoms have been reported at presentation …”
Section: Breast Implant‐associated Anaplastic Large Cell Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…Doren et al 3 reported that lifetime prevalence of BIA-ALCL was approximately 1 in 30,000 for women with textured implants. Other series estimate lifetime risk range from 1:1000 to 1:10,000 in women with textured implants 4 . Up to date, more than 500 cases of BIA-ALCL have been confirmed worldwide 5 ; nevertheless, the exact incidence is difficult to define due to unfamiliarity with this new entity.…”
Section: Introductionmentioning
confidence: 99%